Ordinary Least Square Vs Fixed Effect Regression Model: Studi Empirik Determinan Kebijakan Dividen pada Perusahaan-Perusahaan yang Terdaftar di Bursa Efek Indonesia (BEI) - Caecilia Wahyu E.R. (Universitas Islam Indonesia, 2008)
This research analyzes determinants of corporate dividend policy in Indonesia Stock Exchange (IDX). This research hypothesizes that four financial ratios, which are dividend yield, ROA (return on assets), leverage and PBV (price-to-book value ratio) are determinants of corporate dividend policy.Samples of 25 firms, which are included in many sectors, are all fulfilling data completeness criteria. Research periods are from 2002 until 2006. A balanced panel data study technique is employed to analyze determinants of corporate dividend policy in Indonesia Stock Exchange (IDX). There are two models to estimate regression model used in this research, that is usual Ordinary Least Square (OLS) regression model and the Fixed Effects (FE) or Least Squares Dummy Variable (LSDV) regression model.The study documented that dividend yield, return on assets and leverage have positive effect to dividend payment significantly based on OLS model. Otherwise FE model found dividend yield is the only variable that statistically significant influence dividend payment. The better model to predict determinants of corporate dividend policy is FE model. FE model has higher R-squared value and Durbin-Watson d value than OLS model. In addition, FE model can explain this issue clearly and specifically.Keywords: dividend policy, dividend yield, ROA, leverage, PBV.